2001
DOI: 10.1128/jb.183.2.587-596.2001
|View full text |Cite
|
Sign up to set email alerts
|

DsbA and DsbC Affect Extracellular Enzyme Formation in Pseudomonas aeruginosa

Abstract: DsbA and DsbC proteins involved in the periplasmic formation of disulfide bonds in Pseudomonas aeruginosawere identified and shown to play an important role for the formation of extracellular enzymes. Mutants deficient in either dsbA or dsbC or both genes were constructed, and extracellular elastase, alkaline phosphatase, and lipase activities were determined. The dsbA mutant no longer produced these enzymes, whereas the lipase activity was doubled in the dsbC mutant. Also, extracellar lipase production was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 76 publications
(68 reference statements)
2
52
0
2
Order By: Relevance
“…2) 2 and with the DsbG protein of Chlamydia trachomatis (22) (55 and 53% identical residues and conservative replacements in regions of 171 and 176 amino acids, respectively). In addition, we observed sequence similarity, albeit more limited, with DsbG of E. coli as well as the DsbA proteins of Haemophilus influenzae (23), Neisseria meningitidis (24), and Pseudomonas aeruginosa (25). A further characteristic of several thiol-disulfide oxidoreductases (but not of DsbA of S. aureus), namely a conserved Phe residue at position Ϫ5 relative to the CXXC motif (8,26), is also present in the predicted BdbD protein.…”
Section: The Competence-null Phenotype Of Bfa1074 Is Due To An Insertmentioning
confidence: 71%
“…2) 2 and with the DsbG protein of Chlamydia trachomatis (22) (55 and 53% identical residues and conservative replacements in regions of 171 and 176 amino acids, respectively). In addition, we observed sequence similarity, albeit more limited, with DsbG of E. coli as well as the DsbA proteins of Haemophilus influenzae (23), Neisseria meningitidis (24), and Pseudomonas aeruginosa (25). A further characteristic of several thiol-disulfide oxidoreductases (but not of DsbA of S. aureus), namely a conserved Phe residue at position Ϫ5 relative to the CXXC motif (8,26), is also present in the predicted BdbD protein.…”
Section: The Competence-null Phenotype Of Bfa1074 Is Due To An Insertmentioning
confidence: 71%
“…role in the maturation of extracellular enzymes (Urban et al, 2001), while ppsA (PP2082) encodes phosphoenolpyruvate synthase (PpsA), a key enzyme in gluconeogenesis from aketo acids (Chao et al, 1993).…”
Section: Ligand-binding Properties Of the Aatj Solute Receptormentioning
confidence: 99%
“…The enzyme contains two cysteine residues which form a disulfide bond (20). Recently, it has been shown that this lipase is not secreted in a P. aeruginosa mutant strain devoid of the oxidoreductase DsbA, indicating the importance of the disulfide bond-forming system to the secretion of this enzyme (41). Here, we show by construction and characterization of cysteine-to-serine variants that the primary function of the disulfide bond in P. aeruginosa lipase is to stabilize the protein during and after translocation over the outer membrane.…”
mentioning
confidence: 99%